Ionospheric Specification and Space Weather Forecasting With an HF Beacon Network in the Peruvian Sector - Hysell, D. L. (2018)
A network of high‐frequency (HF) transmitters and receivers used for ionospheric specification is being installed in Peru. The HF transmitters employ multiple frequencies and binary phase coding with pseudorandom noise, and the observables provided by the receivers include group delay, Doppler shift, amplitude, bearing (from interferometry), and polarization. Statistical inverse methods are used to estimate F region density in a volume from the data regionally. The method incorporates raytracing based on the principles of Hamiltonian optics in the forward model and involves an ionospheric parametrization in terms of Chapman functions in the vertical and bicubic B‐spline interpolation in the horizontal. Regularization is employed to minimize the global curvature of the reconstructions. HF beacon data for two nights in January 2018 are presented. We use the reconstructions to investigate why plasma irregularities associated with equatorial spread F formed on one occasion and not the other. The data indicate that the background ionospheric flow is not simply frozen in, that is, that longitude and local time variations cannot be equated, even at regional scales. This has ramifications for equatorial spread F forecasting strategies that assume equivalence.